The Impact of Climate Change on Indonesia’s Food Security Strategy Undertaken by Bulog in 2023 - Manurung, Gerson; Sastrodiharjo, Istianingsih; Hendayana, Yayan (Dinasti International Journal of Economics, Finance & Accounting, 2024)
Climate change affects food security because it causes a shift in the rainy or dry season, which greatly affects the pattern and timing of planting food crops. A decrease in agricultural production will trigger an increase in food prices, which in turn will lead to a decrease in household food purchasing power. Bulog, in this case as the party appointed by the government to carry out activities to maintain the Basic Purchase Price for grain, stabilize prices, especially basic prices, distribute rice for social assistance (Bansos) and manage food stocks, has several strategies to overcome this problem. This study aims to identify the impact of climate change on Indonesia's food security strategy undertaken by Bulog in 2023. The research methodology is based on secondary data that includes a literature review of, articles, e-books, open access e-journals, and previous research. The results showed the influence of climate change on the strategy of Bulog in maintaining food security despite declining production by 1) encouraging subsidiaries by Badan Usaha Milik Negara (BUMN) to increase domestic rice production, 2) building 10 rice milling centers, 7 rice processing centers to its logistics, 3) Distribution of rice assistance of 10 kg per month for low-income groups Program, 4) Stabilization of Food Price Supply (Stabilisasi Pasokan Harga Pangan), which supplies more than 1 million tons of rice at a lower price than the market price. The implication of this research is the importance of strategies to increase domestic food production, strengthen food distribution infrastructure, and pay attention to low-income groups in food assistance programs to overcome the impact of climate change on Indonesia's future food security.